Rationalizing ethnopharmacological uses of Alternanthera sessilis: A folk medicinal plant of Pakistan to manage diarrhea, asthma and hypertension. (22nd April 2016) - Saqib, Fatima; Janbaz, Khalid Hussain
Abstract: Ethnopharmacological relevance: Tribal herbal practitioners of Pakistan use Alternanthera sessilis (Amaranthaceae) to treat diarrhea, asthma and hypertension. Objective: The current study was conducted to provide mechanistic basis for anti-spasmodic, anti- asthmatic and anti-hypertensive use of Alternanthera sessilis . Materials and methods: The crude ethanolic extract of Alternanthera sessilis (As.Cr) and its fractions were tested in- vitro on isolated rabbit tissue preparations (i.e., jejunum, trachea, and aorta) and in-vivo in ketamin-diazepam anaesthetized normotensive rats.The responses were recorded using isotonic and isometric transducers coupled with Power Lab data acquisition system. Results: On isolated rabbit jejunum preparations, As.Cr exerted concentration-dependent (0.01–1.0 mg/ml) spasmolytic effect and caused relaxation of K + (80 mM)-induced spastic contractions. Furthermore, there was non-parallel shift in Ca ++ concentration response curves (CRCs) towards right at tissue bath concentrations of 0.1 and 0.3 mg/ml. On isolated rabbit trachea, it relaxed carbachol (1 μM)- and K +( 80 mM)-induced contractions at respective tissue bath concentrations of 5.0 and 1.0 mg/ml. On isolated rabbit aorta, it also demonstrated relaxant effect on phenylephrine (1 μM)- and K +( 80 mM)-induced contractions at tissue bath concentrations of 5.0 and 3.0 mg/ml respectively. These findings were found to be comparable with verapamil, a reference Ca ++ channel blocker (CCB). The solvent-solvents fractionation revealed domination of spasmolytic effects in dichloromethane fraction as compared to aqueous fraction. Intravenous administration of As.Cr decreased mean arterial blood pressure, systolic blood pressure and diastolic blood pressure of ketamine-diazepam anaesthetized normotensive albino rats dose-dependently, at dose range of 1–10 mg/kg. Conclusion: Our results reflected presence of Ca ++ channel blocking (CCB) activity in As.Cr, thus rationalizing medicinal use of Alternanthera sessilis in diarrhea, asthma and hypertension. Graphical abstract: